Design, synthesis and anti-HIV-1 RT evaluation of 2-(benzyl(4-chlorophenyl)amino)-1-(piperazin-1-yl)ethanone derivatives. Issue 1 (1st January 2017) - Chander, Subhash; Wang, Ping; Ashok, Penta; Yang, Liu-Meng; Zheng, Yong-Tang; Sankaranarayanan, Murugesan
Graphical abstract: Highlights: Fourteen novel compounds were designed, synthesized, and evaluated for HIV-1 RT inhibition. Tested compounds displayed significant to weak potency against the selected target. Among top five RT inhibitors, four retained significant potency against HIV-1 with good safety index. Docked view of compound7m with RT revealed prominent pi-pi stacking and hydrophobic interaction. Abstract: In this study, using molecular hybridization approach, fourteen novel 2-(benzyl(4-chlorophenyl)amino)-1-(piperazin-1-yl)ethanone derivatives (7a –n) were designed as inhibitor of HIV-1 RT. The binding affinity of the designed compounds with HIV-1 RT as well as their drug-likeness behavior was predicted using in-silico studies. All the designed compounds were synthesized, characterized and in-vitro evaluated for HIV-1 RT inhibitory activity, in which tested compounds displayed significant to weak potency against the selected target. Moreover, best active compounds of the series, 7k and7m inhibited the activity of RT with IC50 values 14.18 and 12.26 μM respectively. Structure Activity Relationship (SAR) studies were also performed in order to predict the influence of substitution pattern on the RT inhibitory potency. Anti-HIV-1 and cytotoxicity studies of best five RT inhibitor (7a, 7d, 7k, 7L and7m ) revealed that, except compound7d other compounds retained significant anti-HIV-1 potency with good safety index. Best scoring pose of compound7m was analysed in order to predict its putative binding mode with wild HIV-1 RT.